2004
DOI: 10.1590/s0004-27302004000300013
|View full text |Cite
|
Sign up to set email alerts
|

Hormônio do crescimento ou somatotrófico: novas perspectivas na deficiência isolada de GH a partir da descrição da mutação no gene do receptor do GHRH nos indivíduos da cidade de Itabaianinha, Brasil

Abstract: RESUMOAlém de influenciar o crescimento corpóreo, o hormônio do crescimento, ou somatotrófico, desempenha importante papel no metabolismo, composição corporal, perfil lipídico, estado cardiovascular e longevidade. Seu controle é multi-regulado por hormônios, metabólitos e peptídeos hipotalâmicos. Dados sobre a Deficiência Isolada de GH (DIGH) obtidos a partir da descrição da mutação IVS1+1G→A no gene do receptor do hormônio liberador do GH (GHRH-R) em indivíduos da cidade de Itabaianinha, SE, são revisados. Sã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…In Itabaianinha County, in the north‐eastern Brazilian state of Sergipe, we have identified an extended pedigree with approximately 100 individuals over seven generations with severe isolated GHD (IGHD) due to a homozygous null mutation (IVS1 + 1G → A) in the GHRH receptor (GHRH‐R) gene ( GHRH‐R ). All these subjects have very low serum GH and IGF‐1 levels at birth, resulting in severe short stature, with adult height ranging from 107 to 136 cm (–9·6 to –5·2 SD below normal) 4–6 . As many of the adult subjects from this kindred have never received GH treatment, they offer a unique opportunity to evaluate the final size of abdominal organs in the almost complete absence of GH and IGF‐1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Itabaianinha County, in the north‐eastern Brazilian state of Sergipe, we have identified an extended pedigree with approximately 100 individuals over seven generations with severe isolated GHD (IGHD) due to a homozygous null mutation (IVS1 + 1G → A) in the GHRH receptor (GHRH‐R) gene ( GHRH‐R ). All these subjects have very low serum GH and IGF‐1 levels at birth, resulting in severe short stature, with adult height ranging from 107 to 136 cm (–9·6 to –5·2 SD below normal) 4–6 . As many of the adult subjects from this kindred have never received GH treatment, they offer a unique opportunity to evaluate the final size of abdominal organs in the almost complete absence of GH and IGF‐1.…”
Section: Introductionmentioning
confidence: 99%
“…All these subjects have very low serum GH and IGF-1 levels at birth, resulting in severe short stature, with adult height ranging from 107 to 136 cm (-9·6 to -5·2 SD below normal). [4][5][6] As many of the adult subjects from this kindred have never received GH treatment, they offer a unique opportunity to evaluate the final size of abdominal organs in the almost complete absence of GH and IGF-1. We have already shown that these subjects have decreased limb size 6 and head circumference, reduced pituitary volume, 7 decreased thyroid volume 8 and decreased cardiac size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the largest cohort of patients with IGHD described to date. This mutation leads to a complete abolition of the GHRHR function and consequently affects GH secretion (Souza et al, 2005), leading to very low levels of GH and IGF-I (Aguiar-oliveira et al, 1999; Salvatori et al, 2006). These IGHD individuals have proportional short stature, doll face, high-pitched voices, and central obesity (Aguiar-Oliveira and Bartke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O GH tem importantes funções no organismo, além do papel que lhe sugere o nome (3). Neste trabalho será analisado o papel do GH sobre o crescimento, a composição corporal, os metabolismos lipídico, glicídico e ósseo, o risco cardiovascular, a vida reprodutiva e a qualidade de vida.…”
Section: Introductionunclassified